Financial Transaction and Fiduciary Obligation: Ethics, Economics or Commingled Commitment? - Palliam, Romila; Lee, Caldwell; Ghosh, Dilip K. (UUM Press, 2012)
Financial transactions and fiduciary obligations are simply intertwined. Fiduciaries are subject to the principle of fidelity. It appears, at times at least, public trust in fiduciary commitments is declining as a result of fiduciaries’ selective reporting of financial events and the existence of conflicts when fiduciaries have selfish motives: motives being not always to maximize the trusting party’s value. It is the agency problem. This work attempts to enunciate that commitments and fiduciary obligations emanating from initial financial transactions are not to be violated or ignored as a matter of policy or practice. The questions that arise are: Should a fiduciary be obliged to guarantee a certain outcome for the counter-party, and should a fiduciary be held accountable to a certain type of outcome? We examine what the guidelines are or should be put in place. Initially, under the garb of some socio-religions edicts-cum-dicta, and then under the well-known economic analytics, we make our points and move the view to the forefront.